From nutrition to sustainability: a scoping review on integrated approaches to food and diet - Dicu, Anca (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
In the past decade, bringing together nutrition and sustainability has emerged as a core priority for worldwide research, policy, and practice. Dietary decisions are not merely viewed as personal health choices but as decisions embedded in ecological, social, and psychological systems. While attention to sustainable food systems and diets is growing, evidence remains fragmented across disciplines and settings. This scoping review mapped the literature on integrated food and nutrition strategies to sustainable development systematically. According to PRISMA-ScR, we searched the Web of Science Core Collection and its ancillary sources and identified 55 included studies published from 2000 to 2025. Studies included were systematic reviews, scoping reviews, global modeling studies, and empirical psycho-nutritional studies. Data were synthesized thematically, establishing major conceptual frameworks, policy interventions, educational and behavior drivers, and health dimensions. The review identified four general clusters of themes: (1) integrated nutrition-environment models using multidimensional measurement; (2) policy and institutional actions with sustainability included in health systems and governance; (3) school, professional, and consumer focused educational and behavior change strategies; and (4) psycho-nutritional research into emotional, cognitive, and mental health determinants of sustainable food eating behaviors. Although there has been significant progress, problems remain in standardized measures, cross-sectorial implementation, and psychological and pedagogic integration. Sustainable food systems can be realized only through embracing holistic, interdisciplinary, and context-sensitive strategies that integrate human health, social justice, and planetary well-being. This review highlights key knowledge gaps and calls for advancement in research, policy, education, and practice to drive the shift towards sustainable nutrition worldwide.